Income Distribution: Importance, Forms and Link Between Them - Mavrov, Hristo (Research Papers, 2020)
The paper illustrates in the historical context the evolution of the understanding of the importance of income distribution for economic development and also the reasons for underestimating this problem from economic science. Based on a regression analysis for ten OECD countries, a strong correlation between the functional and personal distribution of income has been established. The theoretical justification and modeling of this relationship is a forthcoming task of economic theory.
Keywords: Income inequality; Functional income distribution; Personal income distribution